2021
DOI: 10.2298/tsci200521250h
|View full text |Cite
|
Sign up to set email alerts
|

Composite design and thermal comfort evaluation of safety helmet with phase change materials cooling

Abstract: Higher temperature and humidity will adversely affect the thermal comfort of helmet users. In order to improve the comfort level of the helmet and obtain an optimal cooling helmet model, four kinds of helmet models were established by using phase-change material (PCM) heat-absorbing cooling technology and fan cooling technology. Through the air conditioning system, the working states of four kinds of helmet models in the thermal environment of 30? were simulated, and the thermal comfort of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The practical results were conducted within a climatic environment where the temperature of 30°C decreased when wearing the helmet and jacket to 22°C. Hu et al [26] suggested a cooling helmet dedicated to the head. The study's objectives were to design a cooling helmet suitable for workers and people.…”
Section: Related Workmentioning
confidence: 99%
“…The practical results were conducted within a climatic environment where the temperature of 30°C decreased when wearing the helmet and jacket to 22°C. Hu et al [26] suggested a cooling helmet dedicated to the head. The study's objectives were to design a cooling helmet suitable for workers and people.…”
Section: Related Workmentioning
confidence: 99%
“…PCMs have thermal characteristics of heat absorption at high temperature and heat release at low temperature 15 . Accordingly, PCMs have been widely used for building heating, 16 solar energy utilization, 17 and agricultural production 18 .…”
Section: Introductionmentioning
confidence: 99%
“…PCMs have thermal characteristics of heat absorption at high temperature and heat release at low temperature. 15 Accordingly, PCMs have been widely used for building heating, 16 solar energy utilization, 17 and agricultural production. 18 Some scholars have attempted to combine PCMs with solar air collectors and use the thermal characteristics of PCMs to carry out heat peak migration aimed at ultimately extending the heat release time of solar air collectors to meet the building users' continuous heating needs.…”
mentioning
confidence: 99%
“…Helmet cooling with PCM is widely considered as an inexpensive, compact, reliable and simple solution to implement [15,16,17,18,19].…”
Section: Phase Change Materials Definitionmentioning
confidence: 99%
“…Many researchers have investigated the effectiveness of using PCM cooling techniques for motorcycle helmets, safety, and construction helmets [15,16,17,18,19]. But there is not much literature on using PCM cooling techniques for football helmets.…”
Section: Pcm Cooled Helmet Systemsmentioning
confidence: 99%